Role of intravenous esmolol, fentanyl and lignocaine for attenuation of stress response in tracheal intubation - a comparative study - Islam, Nurul; Islam, Amirul; Ali, Idris; Shumon, Mohiuddin; Hossain, Mozaffor; Khatun, UH Shahera (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Endotracheal intubation is an essential part of safe airway management but this stimulates the patients airway reflexes and predictably leads to haemodynamic derangement. Many drugs have been suggested in modifying in haemodynamic responses to laryngoscopy and intubation. Objectives To assess efficacy of three drugs - esmolol, fentanyl and lignocaine and to assess which one is more effective to attenuate haemodynamic response to direct laryngoscopy and endotracheal intubation. Methods A total number of 90 patients ASA class I and II were selected randomly as per inclusion and exclusion criteria in three groups, 30 patients in each group. Group A received esmolol 1.5mg/kg in the volume of 10ml (with distil water) 2min before intubation, group B received fentanyl 1.5mg/kg IV 5min before intubation and group C received lignocaine 1.5mg/kg IV 90 sec before intubation. Per-operative data were recorded at 1min, 2min, 5min and 10min after intubation. Results The mean heart rate, systolic, diastolic,mean arterial pressure before starting anaesthesia were similar in group-A (esmolol), B(fentanyl) and C(lignocaine). The mean values of heart rate and rate pressure product were significantly lower in group A(Esmolol) at 1 and 2 minute than group B(fentanyl) and at 1, 2 and 5 minute than group C(lignocaine). The mean values of systolic, diastolic and mean arterial pressure were slightly lower in group A(esmolol) at 5 minute than group B(fentanyl) and significantly lower at 1, 2 and 5 minute than group C(lignocaine). Conclusion Esmolol 1.5mg/kg is superior to lignocaine 1.5mg/kg for attenuation of haemodynamic response (HR, SBP, DBP, RPP and MAP) to laryngoscopy and endotracheal intubation and also superior to fentanyl for attenuation of HR and RPP. DOI: http://dx.doi.org/10.3329/jbsa.v26i1.19810 Journal of Bangladesh Society of Anaesthesiologists 2013; 26(1): 12-19